The Visual Rhetoric in Comics for Reader Interpretation and Engagement to Meaning-Making in the Medium - Muliyati Binti Mat Alim, Ida Puteri binti Mahsan, Mohd Fauzi Bin Harun (Tanjung Malim, 2024)
The Visual Rhetoric in Comics for Reader Interpretation and Engagement to Meaning-Making in the Medium by Muliyati Binti Mat Alim, Ida Puteri binti Mahsan, Mohd Fauzi Bin Harun